Synthesis of a sucrose-based macrocycle with unsymmetrical monosaccharides "arms" - Tiara, Karolina; Potopnyk, Mykhaylo A.; Jarosz, Sławomir (Beilstein Journal of Organic Chemistry, 2018)
An efficient methodology for the selective substitution of both terminal positions (C6 and C6’) in 1’,2,3,3’,4,4’-hexa-O-benzylsucrose with different unsaturated monosaccharide units is presented. Such a highly functionalized intermediate was cyclized under RCM conditions to afford a macrocyclic derivative containing a 31-membered ring in 26% yield.
Keywords: chiral macrocycles; ring-closing metathesis; sucrose